Excess capital and liquidity management - Jan Toporowski (Levy Economics Institute of Bard College, 2008)
These notes present a new approach to corporate finance, one in which financing is not determined by prospective income streams but by financing opportunities, liquidity considerations, and prospective capital gains. This approach substantially modifies the traditional view of high interest rates as a discouragement to speculation; the Keynesian and Post-Keynesian theory of liquidity preference as the opportunity cost of investment; and the notion of the liquidity premium as a factor in determining the rate of interest on longer-term maturities.
Keywords: 330